Pengaruh Struktur Aktiva, Profitabilitas, Kebijakan Dividen Terhadap Struktur Modal Pada Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2005-2009 - Gita Cahya Puspita; Rohmawati Kusumaningtias (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractBanking capital structure has an important role in running a business to run the operations. Given the many factors that affect the company's capital structure research will examine the influence of asset structure, profitability and dividend policy on capital structure in corporate banking. The purpose of this study is to investigate and examine the effect of asset structure, profitability, dividend policy and capital structure of banks listed on the Indonesia Stock Exchange (BEI) in the period 2005 to 2009. The samples used were 7 banking company, where the method used was purposive sampling. Analysis of test data using multiple linear regression. The results indicate that simultaneously asset structure, profitability and dividend policy affects capital structure. While partially variables that affect the capital structure is the structure of assets and profitability, while the partial dividend policy variables do not affect the capital structure.